Etiology and pathophysiology of gestational diabetes mellitus - Kühl, C; Hornnes, P J; Andersen, O (Diabetes (New York, N.Y.), 1985)
In pregnancy, several physiologic changes take place, the sum of which tends to reset the glucose homeostasis in the direction of diabetes. About 1-2% of all pregnant women develop an abnormal glucose tolerance in pregnancy, but most often glucose tolerance returns to normal postpartum. This condition is called gestational diabetes mellitus (GDM). The possibility that glucose tolerance deteriorates in pregnancy because of diabetes-like changes in the secretory function of the endocrine pancreas has been investigated in healthy controls and in normal-weight gestational diabetic subjects. The insulin responses to oral glucose and mixed meals are equally large in these two groups, but the insulin response per unit of glycemic stimulus is significantly lower in the gestational diabetic subjects than in the controls. Diabetes-like changes in glucagon secretion are not observed in either group. Insulin degradation is unaffected by human pregnancy and the proinsulin share of the total plasma insulin immunoreactivity does not increase in pregnancy. Insulin receptor binding to monocytes from normal pregnant women is increased in midpregnancy but is significantly decreased in late pregnancy. No difference in insulin binding (at tracer insulin concentration) to monocytes from healthy pregnant controls and gestational diabetic subjects is found. The insulin concentration necessary to reduce tracer insulin binding by 50% (ID50) is lower in the gestational diabetic subjects diagnosed in late pregnancy than in the pregnant controls. Together, these findings indicate that the number of insulin receptors on monocytes is decreased in GDM at this stage of pregnancy.